2020
DOI: 10.1111/1440-1681.13268
|View full text |Cite
|
Sign up to set email alerts
|

Selenium supplementation during pregnancy and lactation promotes metabolic changes in Wistar rats' offspring

Abstract: Epidemiological and animal studies have demonstrated a strong association between selenium (Se) supplementation and metabolic disorders, we aimed to evaluate whether maternal Se supplementation was able to change metabolic parameters in rats' offspring. Moreover, as Se is a deiodinase (DIO) cofactor, we decided to investigate how thyroid hormones (THs) would be involved in such metabolic changes.Thereby, two groups (n = 6, ~250 g) of female Wistar rats underwent isotonic saline or sodium selenite (1 mg/kg, p.o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Selenoproteins related to oxidative stress, such as glutathione peroxidase, thioredoxin reductase and deiodinase, seem to be important for the changes in GDM 22 . With the increasing incidence rate of GDM, an increasing number of studies have been conducted on animal models, and the physiological and pathological mechanisms of GDM have been evaluated in humans 23–25 . Exploration of the relationship between GDM and serum selenium level and its possible mechanism can provide solutions to reduce the incidence rate of GDM in the future.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Selenoproteins related to oxidative stress, such as glutathione peroxidase, thioredoxin reductase and deiodinase, seem to be important for the changes in GDM 22 . With the increasing incidence rate of GDM, an increasing number of studies have been conducted on animal models, and the physiological and pathological mechanisms of GDM have been evaluated in humans 23–25 . Exploration of the relationship between GDM and serum selenium level and its possible mechanism can provide solutions to reduce the incidence rate of GDM in the future.…”
Section: Introductionmentioning
confidence: 99%
“…22 With the increasing incidence rate of GDM, an increasing number of studies have been conducted on animal models, and the physiological and pathological mechanisms of GDM have been evaluated in humans. [23][24][25] Exploration of the relationship between GDM and serum selenium level and its possible mechanism can provide solutions to reduce the incidence rate of GDM in the future. Although there has been a previous metaanalysis 26 with several of studies on the effects of micronutrients on GDM, we still believe that restart of this analysis is warranted.…”
mentioning
confidence: 99%
“…These authors concluded that cardiovascular alterations took place when IUGR appear and that they are probably related to the impaired thyroid dysfunction that Se deficiency offspring present by decreasing the activity of the selenoproteins DIOs [ 120 , 121 ]. Laureano-Melo et al observed that maternal Se supplementation to Wistar rats was able to program carbohydrate and lipid metabolism, endocrine homeostasis, and feeding behavior, even in the adult offspring [ 122 ]. They suggested that metabolic effects were induced by THs disbalance together with the antioxidant mechanisms.…”
Section: Metabolic Programming and Sementioning
confidence: 99%
“…Adequate ingestion of Se is basic nutrition, as its deficiency results in pregnancyrelated complications, metabolic disorders, and other disorders in offspring (108,109). Melo et al found that in rats, maternal Se increases insulin secretion and glucose tolerance at 80 days of age (110). However, Zeng et al found that excessive Se in the mother's diet led to insulin resistance in offspring at 112 days of age (111).…”
Section: Seleniummentioning
confidence: 99%